Charge Carrier Transport Behavior and Dielectric Properties of BaF2:Tb3+ Nanocrystals - Xiaoyan Cui (Nanomaterials, 2020)
The charge carrier behavior and dielectric properties of BaF2:Tb3+ nanocrystals have been studied by alternating current (AC) impedance spectroscopy. The electron and ion coexist in the transport process. The F− ion’s contribution to the total conduction increases with the doping concentration up to 4% and then decreases. Tb doping leads to the increase of defect quantities and a variation of charge carrier transport paths, which causes the increase of the ion diffusion coefficient and the decreases of bulk and grain boundary resistance. When the Tb-doped concentration is higher than 4%, the effect of deformation potential scattering variation on the transport property is dominant, which results in the decrease of the ion diffusion coefficient and increases of bulk and grain boundary resistance. The conduction properties of our BaF2:Tb3+ nanocrystals are compared with previous results that were found for the single crystals of rare earth-doped BaF2. Tb doping causes increases of both the quantity and the probability of carrier hopping, and it finally leads to increases of BaF2 nanocrystals’ permittivity in the low frequency region.